Lies like wildfire - Alvarez, Jennifer Lynn (Delacorte Press, 2021)
When Hannah and her best friends accidentally spark an enormous and deadly wildfire, their instinct is to lie, but as the blaze roars through their rural town, Hannah's friends begin to crack and one ends up missing.